Legal Guarantees for the Protection of Patient Confidentiality: A Cross-Jurisdictional Study - Benseghir, Mourad; Bentria, Maamar; Sarhan, Adnan Ibrahim; Luhaibi, Salih Ahmed; Yousif, Alaa Yakoob (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2026)
This study examines the legal guarantees governing the confidentiality of patient information in Indonesia and the United Arab Emirates (UAE), two jurisdictions undergoing rapid digital transformation in their healthcare sectors. As the adoption of electronic medical records, telemedicine, and health information systems expands, concerns surrounding the protection, governance, and misuse of patient information have intensified. Through a normative and comparative legal method, this research analyzes the primary legislative instruments, regulatory mechanisms, and institutional arrangements that safeguard patient confidentiality in both countries. The UAE has established a more unified and structured legal framework, particularly through Federal Law No. 2 of 2019 on the Use of Information and Communication Technology (ICT) in Health Fields and the Personal Data Protection Law No. 45 of 2021, which impose stringent obligations for secure processing, access limitation, and data governance. Indonesia, on the other hand, has introduced key regulations such as the Health Law No. 17 of 2023, Minister of Health Regulation No. 24 of 2022 on Medical Records, and the Personal Data Protection Law No. 27 of 2022; however, challenges persist in enforcement consistency, system interoperability, and institutional capacity. By comparing legal standards, confidentiality obligations, penalties for violations, and enforcement practices, this study highlights the strengths and weaknesses of both frameworks. The findings underscore the need for Indonesia to enhance regulatory coherence, improve oversight mechanisms, and adopt best-practice elements from the UAE to reinforce patient information protection